Взаємодія вчителя та асистента вчителя в інклюзивному середовища початкової школи - Греба Ілдіко; Greba Ildikó (Видавництво «Код», 2024)
Резюме. В статті розглядається аналіз взаємодії вчителя та асистента вчителя в інклюзивному освітньому середовища початкової школи. В роботі асистент вчителя розглядається як ключовий учасник ефективної організації освітнього процесу, його роль в адаптації чи модифікації та індивідуалізації освітньої траєкторії учнів з ООП.

Abstract. The article examines the interaction between the teacher and the teacher’s assistant in the inclusive educational environment of primary school. The teacher’s assistant is considered to be the key participant in the effective organization of the educational process, particularly in the adaptation, modification, and individualization of educational trajectories for students with special educational needs (SEN). The study explores specific regulatory documents governing the introduction of the teacher’s assistant position in inclusive classrooms and outlines the primary functions and responsibilities of the assistant in collaboration with the classroom teacher. Additionally, the article analyzes models of co-teaching proposed by the American researcher L. Cook, highlighting the significance of cooperation between the teacher and the assistant in fostering an inclusive learning environment. The co-teaching models discussed in the article within the context of an inclusive educational environment open up new possibilities for enhancing collaboration between the primary teacher and the teacher assistant. The proposed approaches contribute to improving the efficiency of the educational process, fostering individualized learning strategies, and facilitating the integration of students with special educational needs (SEN) into the general secondary education system. Future research should focus on a detailed examination of the step-by-step implementation of coteaching models proposed by L. Cook, taking into account the specific characteristics of the Ukrainian educational landscape. A promising direction includes exploring the practical aspects of adapting these models to different educational levels, age groups, and categories of special needs. A particularly important area of inquiry is the development of methodological recommendations for educators to effectively incorporate co-teaching practices into the operations of inclusive classrooms. Research on the mutual influence of various models on students' academic performance, social integration, and emotional well-being represents an indispensable component of these studies. Moreover, an analysis of teachers' readiness to adopt co-teaching practices, their professional needs, and the level of interaction in inclusive learning environments is vital. Exploring these aspects will facilitate the establishment of a more effective system for training and professional development of teachers and teacher assistants, aligned with the contemporary demands of inclusive education.
Interaction between teacher and teacher’s assistant in the inclusive environment of primary school
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00015039 Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-10
Keywords: індивідуальний підхід; інклюзивна освіта; особливі освітні потреби; рівні можливості; спільне викладання